Analisis Pengendalian Kualitas Produk Paku Kawat Baja Menggunakan Metode Statistical Quality Control dan Failure Mode Effect Analysis di PT. XYZ - Muhammad Miftahul Hamdi; Dwi Sukma Donoriyanto (Ekonomis: Journal of Economics and Business, 2023)
PT. XYZ is a company that produces processed steel wire products such as nails, bendrats and also cutting wire. But in its production, PT. XYZ experienced problems with high levels of defects, especially in nail products in the production section, which resulted in a decrease in quality, waste of production costs, resources and also decreased customer satisfaction. This study aims to determine the percentage of causes of product defects using the Statistical Quality Control (SQC) method and also provide suggestions for improvements using the Failure Mode and Effect Analysis (FMEA) method. The stages in this study begin with collecting data, analyzing data with the SQC method to find the percentage and causes of disability, determining the value of RPN using FMEA, and the recommendation stage for proposed improvements. Based on the results of research on SQC, the most dominant defects are UC (30%), then KTC (21.2%), then BB (19.3%), then UX (15.3%) and KC (14.2%). Based on the results of analysis and calculations in FMEA, it is known that the calculation of the highest RPN value is 336 of the UC defect type with the cause of the position of the bolt standing backwards knife. Based on the results of analysis and calculations in FMEA, it is known that the calculation of the highest RPN value is 336 of the UC defect type with the cause of the position of the bolt standing backwards knife. The proposed improvement recommendation for this problem is to adjust or replace the new knife stand bolt so that the machine will again cut the nail tip perfectly.